2021
DOI: 10.1007/s00430-021-00718-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of experimental and commercial pertussis vaccines in the elimination of Bordetella pertussis isolates with different genetic profiles in murine model

Abstract: The aim of this study was to compare the elimination of Bordetella pertussis clinical isolates, representing different genotypes in relation to alleles encoding virulence factors (MLST—multi-locus antigen sequence typing), MLVA type (multi-locus variable-number tandem repeat analysis) and PFGE group (pulsed-field gel electrophoresis) from the lungs of naive mice or mice were immunised with the commercial whole-cell pertussis vaccine, the acellular pertussis vaccine and the experimental whole-cell pertussis vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Our previous study [38] has shown no pertussis toxin in the Polish DTwP vaccine. In mice immunized with the national DTwP vaccine, no activation of antibodies against the pertussis toxin was observed [38].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our previous study [38] has shown no pertussis toxin in the Polish DTwP vaccine. In mice immunized with the national DTwP vaccine, no activation of antibodies against the pertussis toxin was observed [38].…”
Section: Discussionmentioning
confidence: 86%
“…Our previous study [38] has shown no pertussis toxin in the Polish DTwP vaccine. In mice immunized with the national DTwP vaccine, no activation of antibodies against the pertussis toxin was observed [38]. Since 1978, the Polish DTwP vaccine has been manufactured using three vaccine seeds of B. pertussis strains isolated in the 1960s.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, PRN-deficient B. pertussis also occurs in advanced countries and cause adaptations to aP-vaccinated humans [ 75 ]. The current licensed wP and aP vaccines were found less effective against PRN-deficient isolate than a PRN (+) isolate [ 76 ]. The Tohama I strain, which is usually used in commercial production of aP vaccines, has the ptxP1-ptxA2, prn1, fim2-1, and fim3-1 genotypes, and may have limited cross-protection against genetic variants.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some models may be mildly resistant to nasal colonization, an antibiotic pretreatment to eradicate some usual nasopharyngeal can facilitate the latter and allow for the use of smaller inocula (Soumana et al 2021 ). Pre-immunization may also affect the dose required (Hegerle et al 2014 ; Kang et al 2021 ; Prygiel et al 2021 ). Apart from variation with bacterial strains, the volume of application with nasal inocula led to variation regardless of bacterial load (Halperin et al 1988 ).…”
Section: Non-primate Animal Models Of Pertussismentioning
confidence: 99%
“…Acellular vaccine was found to promote nasal carriage in some studies (Hegerle et al 2014 ; Holubová et al 2020 ). The intranasal model has been used to assess pathogenesis, passive immunity, and vaccination in many studies (Masry 1952 ; Winter 1953 ; Komatsu et al 2010 ; Higgs et al 2012 ; Solans et al 2018 ; Zurita et al 2019 ; Aispuro et al 2020 ; Blackwood et al 2020 ; Rouleau et al 2020 ; Dubois et al 2021 ; Prygiel et al 2021 ). Winter ( 1953 ) also used this model to begin critical studies that would define the specific nature of protective immune responses.…”
Section: Non-primate Animal Models Of Pertussismentioning
confidence: 99%